Biomass‐based Self‐single‐oxygen Heteroatom‐doped Hierarchical Porous Carbon Nanosheets for High‐performance Symmetrical Supercapacitors. Issue 8 (8th July 2022) - Taer, Erman; Taslim, Rika; Apriwandi, Apriwandi
Abstract: Biomass‐based porous carbon holds potential for improving the electrochemical performance of supercapacitors due to its high surface area, 2D nanostructure, 3D hierarchical pores, and self‐multi‐doped‐heteroatoms. Here, 2D and 3D porous carbon nanostructures, as well as self‐single‐doped oxygen were successfully obtained from Moringa oleifera leaves waste by a facile, time‐saving, and cost‐effective strategy. The dried powder precursor was chemically provided with 0.5 m/L H3 PO4 and ZnCl2 solutions at high‐temperature pyrolysis. Furthermore, electrode material was designed with sleekly slim binder‐free solid coins. The obtained porous carbon has a 2D nanosheet‐nanofiber and rich‐3D hierarchical porous structure with significantly high sub‐ultra micropores. Meanwhile, 17.62 % self‐doped oxygen was found to provide an extra pseudocapacitance effect. The optimum carbon possessed high electrochemical properties at a specific capacitance of 201 F g −1 in 1 M H2 SO4 electrolyte. Furthermore, the maximum energy density was obtained at 25 Wh kg −1, at optimum power of 122 W kg −1 in current density of 1.0 A g −1 . The electrochemical behavior of these samples was also reviewed through a 1 M Na2 SO4 neutral aqueous electrolyte. Therefore, the great potential of Moringa oleifera leaves was observed as a porous carbon source with good material properties for enhancing the performance of electrochemical energy storage devices. Abstract : An up‐to‐date strategy was used to synthesize 2D & 3D biomass‐based porous carbon. The hierarchical porous carbon obtained enriches self‐doped oxygen heteroatom. The electrode material was designed without any binder. The symmetric supercapacitor exhibited a specific capacitance of 201 F g −1 .